Functional roles of frugivores and plants shape hyper-diverse mutualistic interactions under two antagonistic conservation scenarios - Fuzessy, Lisieux [UNESP]; Sobral, Gisela; Carreira, Daiane; Rother, Débora Cristina; Barbosa, Gedimar; Landis, Mariana; Galetti, Mauro [UNESP]; Dallas, Tad; Cardoso Cláudio, Vinícius; Culot, Laurence [UNESP]; Jordano, Pedro (Wiley, 2022)
Disentangling the structure of plant–animal mutualisms shed light on how species are organized, and allow us to infer about resilience, specificity, and ultimately the consequences of the loss of functions to the ecosystem. Here we gathered fruit–frugivore interactions for all the major vertebrate taxa interacting with plants in two conservation states in the Brazilian Atlantic forest: a small patch and a continuous forest. Using a network approach, we identified individual roles played by vertebrates and plants, as well as the most relevant functional traits determining the network structure. The most important vertebrates in the continuous forest were the frugivorous characterized by the ability to swallow fruits containing small to large seeds, but they also were the first to be vanished from the small patch decades ago. Animal gape/gullet size, but not body mass, together with the greatest degrees of frugivory contributed to structure the conserved community. In the forest patch, where specialization degrees (in terms of number of interactions performed) were lost, small generalist birds and the only still living primate, along with small lipid-rich fruits, were central in maintaining community structure. This study brings insights on the potential of conserved forests to hold important species-rich interactions, at the same time that small patches count on small birds and small fruits with increased energetic rewards to maintain structuring under human degradation threats. Our results reemphasize the importance of preserving large continuous forest remnants to support important mutualistic interactions subjected to functional traits already lost in small degraded patches. Abstract in Portuguese is available with online material.